COMPARISON OF E-LEARNING WITH STANDARD ATTENDANCE TEACHING AT TECHNICAL UNIVERSITY - HRUSKOVA, Lenka (Journal of Technology and Information Education, 2017)
The study examines the successfulness of e-learning in university education compared to standard full-time classes. The objective of the article is to contribute to the current discussion on the significance and evaluation of digital technologies in the university students studies. Through an empirical research it seeks the answer to the question whether it is more appropriate to use e-learning or standard full-time classes for students of a bachelor's degree programme in the teaching of specialized subjects in a foreign language, whether e-learning is equally successful for males and females in the teaching of specialized subjects in a foreign language or whether there is a correlation between e-learning and fields of studies.
Keywords: e-learning; traditional teaching; specialized language; gender; technical; economic study programs